GhABP19, a Novel Germin-Like Protein From Gossypium hirsutum, Plays an Important Role in the Regulation of Resistance to Verticillium and Fusarium Wilt Pathogens - Pei, Yakun; Li, Xiancai; Zhu, Yutao; Ge, Xiaoyang; Sun, Yun; Liu, Nana; Jia, Yujiao; Li, Fuguang; Hou, Yuxia (Frontiers in Plant Science, 2019)
Germin-like proteins (GLPs) are water-soluble plant glycoproteins belonging to the cupin superfamily. The important role of GLPs in plant responses against various abiotic and biotic stresses, especially pathogens, is well validated. However, little is known about cotton GLPs in relation to fungal pathogens. Here, a novel GLP gene was isolated from Gossypium hirsutum and designated as GhABP19. The expression of GhABP19 was upregulated in cotton plants inoculated with Verticillium dahliae and Fusarium oxysporum and in response to treatment with jasmonic acid (JA) but was suppressed in response to salicylic acid treatment. A relatively small transient increase in GhABP19 was seen in H2O2 treated samples. The three-dimensional structure prediction of the GhABP19 protein indicated that the protein has three histidine and one glutamate residues responsible for metal ion binding and superoxide dismutase (SOD) activity. Purified recombinant GhABP19 exhibits SOD activity and could inhibit growth of V. dahliae, F. oxysporum, Rhizoctonia solani, Botrytis cinerea, and Valsa mali in vitro. To further verify the role of GhABP19 in fungal resistance, GhABP19-overexpressing Arabidopsis plants and GhABP19-silenced cotton plants were developed. GhABP19-transgenic Arabidopsis lines showed much stronger resistance to V. dahliae and F. oxysporum infection than control (empty vector) plants did. On the contrary, silencing of GhABP19 in cotton conferred enhanced susceptibility to fungal pathogens, which resulted in necrosis and wilt on leaves and vascular discoloration in GhABP19-silenced cotton plants. The H2O2 content and endogenous SOD activity were affected by GhABP19 expression levels in Arabidopsis and cotton plants after inoculation with V. dahliae and F. oxysporum, respectively. Furthermore, GhABP19 overexpression or silencing resulted in activation or suppression of JA-mediated signaling, respectively. Thus, GhABP19 plays important roles in the regulation of resistance to verticillium and fusarium wilt in plants. These modulatory roles were exerted by its SOD activity and ability to activate the JA pathway. All results suggest that GhABP19 was involved in plant disease resistance.